Clinicopathologic characteristics of kidney and other organs in ANCA-associated vasculitis patients and outcomes and risk factors - LIU Guo-ping; WANG Chun-yan; XU Li-bin; CAO Sai-xia; GUO Yan (Linchuang shenzangbing zazhi)
Objective To investigate the clinicopathological characteristics of antineutrophil cytoplasmic antibody(ANCA)-associated vasculitis(AAV) with renal involvement and other organs in Inner Mongolia People’s Hospital and to analyze the outcomes and risk factors.Methods Clinical features of 123 cases of AAV hospitalized from September 1995 to September 2009 were reviewed retrospectively.According to the ANCA test results,the patients were divided into cytoplastic ANCA positive group(C-ANCA group) and perinuclear ANCA positive group(P-ANCA group).The differences in clinicopathological manifestations,laboratory tests and functional outcomes were observed.The death and renal failure were the end point in the 5 years.Results Of 123 AAV patients,63 were male,and 60 were female(the male and female ratio was 1.05:1).The age ranged from 38-82 years old.82.9%of them(102 cases) were in the range of 50-82 years old(mean 60 ± 22).109 were PANCA positive,and 14 were C-ANCA positive.Renal involvement and lung involvement were similar between C-ANCA group and P-ANCA group.The prevalence of respiratory,gastrointestinal,articular and ophthalmic involvements was higher in P-ANCA group than in C-ANCA group(P<0.05).There was no significant difference in otologic,cutaneous,muscular and neural involvements between two groups.Of the 62 cases receiving renal biopsy,crescent nephritis was found in 30 cases,glomerrular segmental necrosis in 12 cases,mesenteria crescent in 15 cases,and fabric crescent with focal segmental sclerosis in 15 cases.There was no significant difference in mortality and renal failure between two groups.Respiratory failure and multiple organ dysfunctions were relative mortality factors in the analysis of age,sex,types of ANCA,fever,renal failure,respiratory and lung infection.There were significant relationships between clinical terminus with serum creatinine,erythrocyte sediment rate,plasma-albumin and hemoglobin.Logistic regression analysis revealed that serum creatinine level and erythrocyte sediment rate at the baseline were associated with poor outcomes.Conclusions AAV is common in elders and men with multiple organ involvement P-ANCA positive patients are more than C-ANCA patients.The number of organ involvements in P-ANCA group is greater than that in C-ANCA group.The disease spectrum is different in these two groups.Respiratory failure and multiple organ dysfunctions were relative mortality factors.